Patterns and Predictors of Cognitive Function Among Virally Suppressed Women With HIV - Dastgheyb, Raha M.; Buchholz, Alison S.; Fitzgerald, Kathryn C.; Xu, Yanxun; Williams, Dionna W.; Springer, Gayle; Anastos, Kathryn; Gustafson, Deborah R.; Spence, Amanda B.; Adimora, Adaora A.; Waldrop, Drenna; Vance, David E.; et al. (Frontiers in Neurology, 2021)
Cognitive impairment remains frequent and heterogeneous in presentation and severity among virally suppressed (VS) women with HIV (WWH). We identified cognitive profiles among 929 VS-WWH and 717 HIV-uninfected women from 11 Women's Interagency HIV Study sites at their first neuropsychological (NP) test battery completion comprised of: Hopkins Verbal Learning Test-Revised, Trail Making, Symbol Digit Modalities, Grooved Pegboard, Stroop, Letter/Animal Fluency, and Letter-Number Sequencing. Using 17 NP performance metrics (T-scores), we used Kohonen self-organizing maps to identify patterns of high-dimensional data by mapping participants to similar nodes based on T-scores and clustering those nodes. Among VS-WWH, nine clusters were identified (entropy = 0.990) with four having average T-scores ≥45 for all metrics and thus combined into an “unimpaired” profile (n = 311). Impaired profiles consisted of weaknesses in: (1) sequencing (Profile-1; n = 129), (2) speed (Profile-2; n = 144), (3) learning + recognition (Profile-3; n = 137), (4) learning + memory (Profile-4; n = 86), and (5) learning + processing speed + attention + executive function (Profile-5; n = 122). Sociodemographic, behavioral, and clinical variables differentiated profile membership using Random Forest models. The top 10 variables distinguishing the combined impaired vs. unimpaired profiles were: clinic site, age, education, race, illicit substance use, current and nadir CD4 count, duration of effective antiretrovirals, and protease inhibitor use. Additional variables differentiating each impaired from unimpaired profile included: depression, stress-symptoms, income (Profile-1); depression, employment (Profile 2); depression, integrase inhibitor (INSTI) use (Profile-3); employment, INSTI use, income, atazanavir use, non-ART medications with anticholinergic properties (Profile-4); and marijuana use (Profile-5). Findings highlight consideration of NP profile heterogeneity and potential modifiable factors contributing to impaired profiles.